When Bullets Penetrate Bullet-Proof Vests: Conformity of the Bullet-Proof Material to the Contract of Sale and Concurrent Remedies (a Note on the Judgment of the Multi-Member Court of First Instance of Athens 4505/2009) - Flambouras, Dionysios P. (Journal of Law and Commerce, 2011)
The Vienna Convention of 1980 for the International Sale of Goods (the “Vienna Convention” or “CISG”) was entered into force in Greece on1.2.1999 by virtue of law no. 2532/1997 (Gov. Gazette A 227/11.11.1997) and has since then been applied and interpreted by fourteen Greek judgments. The judgment of the Multi-Member Court of First Instance of Athens 4505/2009 (“Judgment 4505/2009”) is, if not the most important, one of the most important cases. Its importance is based not only on the CISG legal issues on which it expressed an opinion, but also on the particularities (and complexities) of its facts (its original text exceeds 100 pages and is still unpublished in Greece). On this basis the author believes that the full understanding of the legal issues of Judgment 4505/2009 requires systematic and, to the extent possible, detailed presentation of its complicated facts. It is noted that Judgment 4505/2009 also deals with important legal issues relating to international jurisdiction and Greek domestic civil law. However, this note will only concentrate, with few exceptions, on legal issues relating to the CISG.